Development of a Numerical Model of the 9 mm Parabellum FMJ Bullet Including Jacket Failure - MARECHAL, Ch.; BRESSON, F.; HAUGOU, G. (Engineering Transactions, 2011)
Even though ballistic experiments are widely accepted as the only reliable way to probe terminal effects, we demonstrate that computer simulation can be a useful alternative. Particularly, the high energy projectiles are seldom studied in the field of forensic sciences. That situation being favorable to computer simulation, a 3D finite element model of the worldwide-used 9 mm Parabellum bullet has been developed with Abaqus explicit software. A Johnson-Cook constitutive model, fed with the split Hopkinson pressure bar experimental parameters, accurately describes the materials’ behavior (lead and brass). Experiments were performed with a handgun and a hard steel plate target in order to discuss the reliability of the model. Accurate predictions about bullet deformation and failure were obtained without any post-calculation adjustment of parameters.